Monitoring of Public Street Lighting Equipment Using Passive Infrared Receiver (PIR) Sensors and Node-red - Ismail Faruqi , Muhammad; Herjuno, Dimas (Universitas Negeri Surabaya or The State University of Surabaya, 2024)
The current public street lighting system (PJU) still uses manual panel control. With these problems to find out the condition of the lights from the public street lighting (PJU) is running well or not and to find out whether the lights are on or off. From this statement, the purpose of this study is to determine 1) the sensitivity distance of the PIR (Passive Infrared Receiver) sensor with Movement on a microcontroller-based PJU to save electrical energy. 2) comparison of Current When measured using an ampere clamp and Node-red. The method used is experimental, namely Referring to two sets of variables. The first set functions as a constant. The results of the study show that 1) Based on the test results, it was found that the PIR sensor works when the human object is at a distance of 1 to 8 meters and can be detected objects in bright or dark conditions. 2) Based on the test results, it was found that the PZEM-004T sensor When given a load, the greater the current load given to the device, the current value read on the Node-red.